Policy Analysis Reducing Under Five Stunting Children in Special Region Yogyakarta, Indonesia - Siswati, Tri; Murdiati, Agnes (Jurnal Kebijakan Kesehatan Indonesia, 2022)
Yogyakarta Special Region is a provinces with a low prevalence of stunting children in Indonesia as many as 21%. Many policies support reducing stunting children effort. This study aims to analysis of policies related to reduce stunting. The method was desk review using secondary data, literature review, policy/regulation tracing related to stunting children and discussions, presentations, Focus Group Discussion (FGD), and Round Table Discussion (RTD). Causes of stunting include distal factors such as the economy, poverty, education, and well-being. Proximate factors were baby low birth weight and adolescent pregnancy. Interventions conducted with a focus target on 1000 early day life include sensitive and specific nutritional interventions. All regional organization have taken a role in combating stunting. Also regulations both internationally, nationally and regionally support the acceleration of the decline of stunting. But the specific regulations on stunting is not available. Effort to reducing stunting have been implemented but need more synergitic and integrated intervention between regional organization with Bappeda as the leading sector.